Effect of the aqueous extract of Senecio biafrae (Oliv. & Hiern) J. Moore on some fertility parameters in immature female rat. (23rd February 2015) - Lienou, L.L.; Telefo, P.B.; Njimou, J.R.; Nangue, C.; Bayala, B.R.; Goka, S.C.; Biapa, P.; Yemele, M.D.; Donfack, N.J.; Mbemya, J.T.; Tagne, S.R.; Rodrigues, A.P.R.
Abstract: Ethnopharmacological relevance: Senecio biafrae is a plant from the huge family of Asteraceae used in the African pharmacopoeia for the treatment of many ailments among which is infertility. Material and methods: The aqueous extract, which was primarily subjected to polyphenol analysis, has been administered to immature female rats for 20 days at 8, 32, 64 and 128 mg/kg of body weight. The day following the treatment, the animals were sacrificed; their serum, ovary and uterus were retained respectively for reproductive hormones, ovarian and uterine proteins, and ovarian cholesterol assays. Results: Light body weight gain variation of treated animals was observed during the experimental period. A significant increase ( p ˂0.05) in serum estradiol and proteins as well as in uterine weight ( p ˂0.01) of all Senecio biafrae treated animals was noted. No significant variation was noticed in the ovarian weight and follicle numbers. Conclusion: The various biochemical and physiological parameters of fertility were significantly improved with the aqueous extract of Senecio biafrae, thus attesting some of its traditional usage. Graphical abstract: